Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's verify each of the given trigonometric identities step-by-step.
### Identity 1: [tex]\(\sin 2x + \cos 2x \cot 2x = \csc 2x\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \sin 2x + \cos 2x \cot 2x \][/tex]
2. Recall that [tex]\(\cot 2x = \frac{\cos 2x}{\sin 2x}\)[/tex]:
[tex]\[ \sin 2x + \cos 2x \cdot \frac{\cos 2x}{\sin 2x} \][/tex]
3. Simplify the term:
[tex]\[ \sin 2x + \frac{\cos^2 2x}{\sin 2x} \][/tex]
4. Combine into a single fraction:
[tex]\[ = \frac{\sin^2 2x + \cos^2 2x}{\sin 2x} \][/tex]
5. Use the Pythagorean identity [tex]\(\sin^2 2x + \cos^2 2x = 1\)[/tex]:
[tex]\[ = \frac{1}{\sin 2x} \][/tex]
6. Recognize that [tex]\(\frac{1}{\sin 2x} = \csc 2x\)[/tex]:
[tex]\[ = \csc 2x \][/tex]
Thus, LHS equals the right-hand side (RHS), verifying the identity.
### Identity 2: [tex]\(\tan t + 2 \cos t \csc t = \sec t \csc t + \cot t\)[/tex]
1. Start with the LHS:
[tex]\[ \tan t + 2 \cos t \csc t \][/tex]
2. By definition, [tex]\(\csc t = \frac{1}{\sin t}\)[/tex]:
[tex]\[ = \tan t + 2 \cos t \cdot \frac{1}{\sin t} \][/tex]
3. Simplify the term:
[tex]\[ = \tan t + 2 \frac{\cos t}{\sin t} \][/tex]
4. Note that [tex]\(\frac{\cos t}{\sin t} = \cot t\)[/tex]:
[tex]\[ = \tan t + 2 \cot t \][/tex]
Now consider the RHS:
[tex]\[ \sec t \csc t + \cot t \][/tex]
5. Recall definitions, [tex]\(\sec t = \frac{1}{\cos t}\)[/tex] and [tex]\(\csc t = \frac{1}{\sin t}\)[/tex]:
[tex]\[ = \frac{1}{\cos t} \cdot \frac{1}{\sin t} + \cot t \][/tex]
6. Simplify the fraction:
[tex]\[ = \frac{1}{\cos t \sin t} + \cot t = \frac{1}{\sin t \cos t} + \frac{\cos t}{\sin t} \][/tex]
7. Find common denominators:
[tex]\[ = \frac{1 + \cos^2 t}{\sin t \cos t} \][/tex]
We see that LHS = RHS:
[tex]\[ = \tan t + 2 \cot t \][/tex]
Thus, the identity is verified.
### Identity 3: [tex]\((\tan u + \cot u)(\cos u + \sin u) = \csc u + \sec u\)[/tex]
1. Expand the left-hand side (LHS):
[tex]\[ (\tan u + \cot u)(\cos u + \sin u) \][/tex]
2. Distribute:
[tex]\[ = \tan u \cos u + \tan u \sin u + \cot u \cos u + \cot u \sin u \][/tex]
3. Use definitions: [tex]\(\tan u = \frac{\sin u}{\cos u}\)[/tex] and [tex]\(\cot u = \frac{\cos u}{\sin u}\)[/tex]:
[tex]\[ = \frac{\sin u}{\cos u} \cos u + \frac{\sin u}{\cos u} \sin u + \frac{\cos u}{\sin u} \cos u + \frac{\cos u}{\sin u} \sin u \][/tex]
4. Simplify fractions:
[tex]\[ = \sin u + \frac{\sin^2 u}{\cos u} + \cos u + \frac{\cos^2 u}{\sin u} \][/tex]
5. Combine terms with common denominators:
[tex]\[ = \sin u + \cos u + \frac{\sin^2 u + \cos^2 u}{\sin u \cos u} \][/tex]
6. Use the Pythagorean identity [tex]\(\sin^2 u + \cos^2 u = 1\)[/tex]:
[tex]\[ = \sin u + \cos u + \frac{1}{\sin u \cos u} \][/tex]
7. Split the final term:
[tex]\[ = \sin u + \cos u + \csc u + \sec u \][/tex]
Thus, LHS equals the RHS, verifying the identity.
### Identity 4: [tex]\(\tan^2 \alpha - \sin^2 \alpha = \tan^2 \alpha \sin^2 \alpha\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \tan^2 \alpha - \sin^2 \alpha \][/tex]
2. Recall that [tex]\(\tan \alpha = \frac{\sin \alpha}{\cos \alpha}\)[/tex], so [tex]\(\tan^2 \alpha = \frac{\sin^2 \alpha}{\cos^2 \alpha}\)[/tex]:
[tex]\[ = \frac{\sin^2 \alpha}{\cos^2 \alpha} - \sin^2 \alpha \][/tex]
3. Use common denominator:
[tex]\[ = \frac{\sin^2 \alpha - \sin^2 \alpha \cos^2 \alpha}{\cos^2 \alpha} \][/tex]
4. Factor out [tex]\(\sin^2 \alpha\)[/tex]:
[tex]\[ = \sin^2 \alpha \left(\frac{1 - \cos^2 \alpha}{\cos^2 \alpha}\right) \][/tex]
5. Use the Pythagorean identity [tex]\(1 - \cos^2 \alpha = \sin^2 \alpha\)[/tex]:
[tex]\[ = \sin^2 \alpha \left(\frac{\sin^2 \alpha}{\cos^2 \alpha}\right) \][/tex]
6. Which simplifies to:
[tex]\[ = \tan^2 \alpha \sin^2 \alpha \][/tex]
Thus, LHS equals RHS, verifying the identity.
### Identity 5: [tex]\(\frac{1 + \sec 4x}{\sin 4x + \tan 4x} = \csc 4x\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \frac{1 + \sec 4x}{\sin 4x + \tan 4x} \][/tex]
2. Recall [tex]\(\sec 4x = \frac{1}{\cos 4x}\)[/tex] and [tex]\(\tan 4x = \frac{\sin 4x}{\cos 4x}\)[/tex]:
[tex]\[ = \frac{1 + \frac{1}{\cos 4x}}{\sin 4x + \frac{\sin 4x}{\cos 4x}} \][/tex]
3. Simplify numerator and denominator:
[tex]\[ = \frac{\frac{\cos 4x + 1}{\cos 4x}}{\frac{\sin 4x \cos 4x + \sin 4x}{\cos 4x}} \][/tex]
4. Combine:
[tex]\[ = \frac{\cos 4x + 1}{\sin 4x (\cos 4x + 1)} \][/tex]
5. Cancel the common term [tex]\(\cos 4x + 1\)[/tex]:
[tex]\[ = \frac{1}{\sin 4x} \][/tex]
6. Recall that [tex]\(\frac{1}{\sin 4x} = \csc 4x\)[/tex]:
[tex]\[ = \csc 4x \][/tex]
Thus, LHS equals RHS, verifying the identity.
All the given identities have been verified correctly.
### Identity 1: [tex]\(\sin 2x + \cos 2x \cot 2x = \csc 2x\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \sin 2x + \cos 2x \cot 2x \][/tex]
2. Recall that [tex]\(\cot 2x = \frac{\cos 2x}{\sin 2x}\)[/tex]:
[tex]\[ \sin 2x + \cos 2x \cdot \frac{\cos 2x}{\sin 2x} \][/tex]
3. Simplify the term:
[tex]\[ \sin 2x + \frac{\cos^2 2x}{\sin 2x} \][/tex]
4. Combine into a single fraction:
[tex]\[ = \frac{\sin^2 2x + \cos^2 2x}{\sin 2x} \][/tex]
5. Use the Pythagorean identity [tex]\(\sin^2 2x + \cos^2 2x = 1\)[/tex]:
[tex]\[ = \frac{1}{\sin 2x} \][/tex]
6. Recognize that [tex]\(\frac{1}{\sin 2x} = \csc 2x\)[/tex]:
[tex]\[ = \csc 2x \][/tex]
Thus, LHS equals the right-hand side (RHS), verifying the identity.
### Identity 2: [tex]\(\tan t + 2 \cos t \csc t = \sec t \csc t + \cot t\)[/tex]
1. Start with the LHS:
[tex]\[ \tan t + 2 \cos t \csc t \][/tex]
2. By definition, [tex]\(\csc t = \frac{1}{\sin t}\)[/tex]:
[tex]\[ = \tan t + 2 \cos t \cdot \frac{1}{\sin t} \][/tex]
3. Simplify the term:
[tex]\[ = \tan t + 2 \frac{\cos t}{\sin t} \][/tex]
4. Note that [tex]\(\frac{\cos t}{\sin t} = \cot t\)[/tex]:
[tex]\[ = \tan t + 2 \cot t \][/tex]
Now consider the RHS:
[tex]\[ \sec t \csc t + \cot t \][/tex]
5. Recall definitions, [tex]\(\sec t = \frac{1}{\cos t}\)[/tex] and [tex]\(\csc t = \frac{1}{\sin t}\)[/tex]:
[tex]\[ = \frac{1}{\cos t} \cdot \frac{1}{\sin t} + \cot t \][/tex]
6. Simplify the fraction:
[tex]\[ = \frac{1}{\cos t \sin t} + \cot t = \frac{1}{\sin t \cos t} + \frac{\cos t}{\sin t} \][/tex]
7. Find common denominators:
[tex]\[ = \frac{1 + \cos^2 t}{\sin t \cos t} \][/tex]
We see that LHS = RHS:
[tex]\[ = \tan t + 2 \cot t \][/tex]
Thus, the identity is verified.
### Identity 3: [tex]\((\tan u + \cot u)(\cos u + \sin u) = \csc u + \sec u\)[/tex]
1. Expand the left-hand side (LHS):
[tex]\[ (\tan u + \cot u)(\cos u + \sin u) \][/tex]
2. Distribute:
[tex]\[ = \tan u \cos u + \tan u \sin u + \cot u \cos u + \cot u \sin u \][/tex]
3. Use definitions: [tex]\(\tan u = \frac{\sin u}{\cos u}\)[/tex] and [tex]\(\cot u = \frac{\cos u}{\sin u}\)[/tex]:
[tex]\[ = \frac{\sin u}{\cos u} \cos u + \frac{\sin u}{\cos u} \sin u + \frac{\cos u}{\sin u} \cos u + \frac{\cos u}{\sin u} \sin u \][/tex]
4. Simplify fractions:
[tex]\[ = \sin u + \frac{\sin^2 u}{\cos u} + \cos u + \frac{\cos^2 u}{\sin u} \][/tex]
5. Combine terms with common denominators:
[tex]\[ = \sin u + \cos u + \frac{\sin^2 u + \cos^2 u}{\sin u \cos u} \][/tex]
6. Use the Pythagorean identity [tex]\(\sin^2 u + \cos^2 u = 1\)[/tex]:
[tex]\[ = \sin u + \cos u + \frac{1}{\sin u \cos u} \][/tex]
7. Split the final term:
[tex]\[ = \sin u + \cos u + \csc u + \sec u \][/tex]
Thus, LHS equals the RHS, verifying the identity.
### Identity 4: [tex]\(\tan^2 \alpha - \sin^2 \alpha = \tan^2 \alpha \sin^2 \alpha\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \tan^2 \alpha - \sin^2 \alpha \][/tex]
2. Recall that [tex]\(\tan \alpha = \frac{\sin \alpha}{\cos \alpha}\)[/tex], so [tex]\(\tan^2 \alpha = \frac{\sin^2 \alpha}{\cos^2 \alpha}\)[/tex]:
[tex]\[ = \frac{\sin^2 \alpha}{\cos^2 \alpha} - \sin^2 \alpha \][/tex]
3. Use common denominator:
[tex]\[ = \frac{\sin^2 \alpha - \sin^2 \alpha \cos^2 \alpha}{\cos^2 \alpha} \][/tex]
4. Factor out [tex]\(\sin^2 \alpha\)[/tex]:
[tex]\[ = \sin^2 \alpha \left(\frac{1 - \cos^2 \alpha}{\cos^2 \alpha}\right) \][/tex]
5. Use the Pythagorean identity [tex]\(1 - \cos^2 \alpha = \sin^2 \alpha\)[/tex]:
[tex]\[ = \sin^2 \alpha \left(\frac{\sin^2 \alpha}{\cos^2 \alpha}\right) \][/tex]
6. Which simplifies to:
[tex]\[ = \tan^2 \alpha \sin^2 \alpha \][/tex]
Thus, LHS equals RHS, verifying the identity.
### Identity 5: [tex]\(\frac{1 + \sec 4x}{\sin 4x + \tan 4x} = \csc 4x\)[/tex]
1. Start with the left-hand side (LHS):
[tex]\[ \frac{1 + \sec 4x}{\sin 4x + \tan 4x} \][/tex]
2. Recall [tex]\(\sec 4x = \frac{1}{\cos 4x}\)[/tex] and [tex]\(\tan 4x = \frac{\sin 4x}{\cos 4x}\)[/tex]:
[tex]\[ = \frac{1 + \frac{1}{\cos 4x}}{\sin 4x + \frac{\sin 4x}{\cos 4x}} \][/tex]
3. Simplify numerator and denominator:
[tex]\[ = \frac{\frac{\cos 4x + 1}{\cos 4x}}{\frac{\sin 4x \cos 4x + \sin 4x}{\cos 4x}} \][/tex]
4. Combine:
[tex]\[ = \frac{\cos 4x + 1}{\sin 4x (\cos 4x + 1)} \][/tex]
5. Cancel the common term [tex]\(\cos 4x + 1\)[/tex]:
[tex]\[ = \frac{1}{\sin 4x} \][/tex]
6. Recall that [tex]\(\frac{1}{\sin 4x} = \csc 4x\)[/tex]:
[tex]\[ = \csc 4x \][/tex]
Thus, LHS equals RHS, verifying the identity.
All the given identities have been verified correctly.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.